Organizational Change in Public Service - Ekowati, Dian (International Research Journal of Business Studies, 2021)
This study aims to investigate institutional logic underlying the initiation of the change management process in public sector organizations. Organizational Institutionalism is used to frame the analysis. The study itself took place in three different public organizations in the Province of East Java, including a one-stop service for licensing as well as that of vehicle registration, taxing, and insurance and also from the local health authority. The qualitative method was employed to analyze information gathered through semi-structured interviews with 35 respondents. Data were analyzed by using an approach informed by grounded theory. The study unveiled various institutional logics underlying the adoption of changes and innovation in organizations. It ranged from the most common reason for improving performance gaps up to the need to clean the organization’s name and build a better image. The study contributes to the idea that an organization’s previous experiences, as well as perceived institutional character, affect the need to conduct changes.